Jean Baptiste Van Moer (1819-1884), Images of Diocletian’s Palace - Belamarić, Josip (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
Jean Baptiste van Moer was a respected Belgian painter of architecture, interiors, and landscapes. Until recently, the only Van Moer oil painting depicting Split that we knew of was the view of the Peristyle with the sphinx in focus – oil on panel, today in the Archaeological Museum in Split. At several recent auctions, at which Van Moer’s paintings frequently appear, the author noticed a number of paintings for which there are preparatory drawings kept in the National Library in Zagreb. Among them, two oil paintings stand out for their artistic and documentary value. They depict previously unknown details of the northern side of the Peristyle of Diocletian’s Palace. The veduta of the south-eastern part of the Peristyle (painted in 1860) is particularly important because it is the only one to show the polychromatic effect on the remarkable bell tower of the Cathedral of St Domnius. This important original effect was stripped away entirely during the reconstruction works in 1885-1908.